Translating the sacred: literature and ethnography in Carlos Castaneda / Taduzindo o sagrado: literatura e etnografia em Carlos Castaneda - de Lima, Marcel (Numen, 2014)
Abstract This article deals with the debate over the narrative of American anthropologist Carlos Castaneda and the problematic of his Yaqui informant Don Juan. It is my contention that Castaneda’s narrative presents a blend of interdisciplinary discourses involving primarily literature and ethnography. I propose the discussion of whether the traces of fictional narrative to be found in a supposed ethnographic account are meant to work as a form of translation of sacred space, that is, as a challenge at transcribing the unworldly, or simply as a means of representing the concept of power within shamanism as personal amoral gratification. In short, I argue that Castaneda’s narrative could be seen as paradigmatic of the power of language not to originate the supernatural but rather, given the use of certain literary techniques, to attempt at representing that which cannot be grasped by words alone. Keywords: literature, ethnography, supernatural, sacred, hermeneutics Resumo Este artigo lida com o debate envolvendo a narrativa do antropólogo norteamericano Carlos Castaneda e a problemática de seu informante Yaqui Don Juan. É minha contenção que a narrativa de Castaneda apresenta-se como uma mistura de discursos interdisciplinares que envolvem acima de tudo a literatura e a etnografia. Eu proponho a discussão a respeito dos traços ficcionais encontrados numa suposta etnografia como sendo uma forma de tradução do espaço sagrado, ou seja, de um desafio à transcrição do inominável, ou simplesmente como uma maneira de representar o conceito de poder no xamanismo em termos de uma gratificação pessoal amoral. Em suma, eu argumento que a narrativa de Castaneda poderia ser vista como paradigma do poder da linguagem, não como fonte originária do sobrenatural, mas, dado o uso de certas técnicas literárias, como tentativa de representação do que não pode ser apreendido somente pelas palavras. Palavras-Chave: literatura, etnografia, sobrenatural, sagrado, hermenêutica